2007
DOI: 10.1093/jn/137.8.1974
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Isoflavones May Protect against Prostate Cancer in Japanese Men ,

Abstract: We examined associations between nutritional and other lifestyle factors and the prevalence of prostate cancer in a casecontrol study of Japanese men. Two hundred patients and 200 age-matched controls (65 y) were selected from 3 geographic areas of Japan. BMI, physical activity, occupation, family history of prostate cancer, and medical history were not associated with prostate cancer risk. Isoflavones and their aglycones (genistein and daidzein) were significantly associated with decreased risk. The odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…In earlier observational studies, dietary intake of isoflavones or soy product consumption was inversely associated with prostate cancer risk in some (Severson et al, 1989;Jacobsen et al, 1998;Strom et al, 1999;Kolonel et al, 2000a;Lee et al, 2003;Sonoda et al, 2004;Hedelin et al, 2006a;Heald et al, 2007;Kurahashi et al, 2007;Nagata et al, 2007), but not all reports (Sung et al, 1999;Villeneuve Matching for geographic location (Hawaii or California), race/ethnicity, birth year ( ± 1 year), date ( ± 6 months) and time ( ± 2 h) of specimen collection, and fasting hours (0 -o6, 6 -o8, 8 -o10, and 10+ h). The models were adjusted for age at specimen collection and fasting hours as continuous variables, as well as family history of prostate cancer, BMI, and education.…”
Section: Discussionmentioning
confidence: 98%
“…In earlier observational studies, dietary intake of isoflavones or soy product consumption was inversely associated with prostate cancer risk in some (Severson et al, 1989;Jacobsen et al, 1998;Strom et al, 1999;Kolonel et al, 2000a;Lee et al, 2003;Sonoda et al, 2004;Hedelin et al, 2006a;Heald et al, 2007;Kurahashi et al, 2007;Nagata et al, 2007), but not all reports (Sung et al, 1999;Villeneuve Matching for geographic location (Hawaii or California), race/ethnicity, birth year ( ± 1 year), date ( ± 6 months) and time ( ± 2 h) of specimen collection, and fasting hours (0 -o6, 6 -o8, 8 -o10, and 10+ h). The models were adjusted for age at specimen collection and fasting hours as continuous variables, as well as family history of prostate cancer, BMI, and education.…”
Section: Discussionmentioning
confidence: 98%
“…Isoflavones are one of the phytoestrogens that are possible preventive factors in several hormone-dependent cancers such as prostate cancer and breast cancer (Zhu et al, 2011;Khan et al, 2012 ), cardiovascular disease (Wong et al, 2012;Usui et al, 2013), menopausal symptoms (Aso et al, 2012;Jenks et al, 2012), and osteoporosis (Scheiber et al, 2001;Tousen et al, 2011). Especially, genistein and daidzein, which are aglycones of isoflavones, were found to have potential roles in the prevention of prostate cancer (Akaza et al, 2004;Nagata et al, 2007;Gardner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These polyphenolic compounds bind to estrogen receptors alpha and beta, with a preference for the latter [4]. Several epidemiological studies have suggested that high phytoestrogen levels are associated with a reduced risk of hormone-sensitive diseases [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%